2008
DOI: 10.1097/aco.0b013e3283184227
|View full text |Cite
|
Sign up to set email alerts
|

Review of video laryngoscopy and rigid fiberoptic laryngoscopy

Abstract: As indirect laryngoscopic tools become more available, and clinicians become more facile in their use, the management of (potentially) difficult intubations is likely to change. Further technological advances are likely to lead to the development of even more new instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 66 publications
2
64
2
1
Order By: Relevance
“…Les donne´es suivantes ont e´te´mesure´es et enregistre´es : temps jusqu'a`intubation trache´ale re´ussie (crite`re d'e´valuation principal), taux de re´ussite global, temps jusqu'a`visualisation des cordes vocales, pourcentage d'ouverture glottique, compression dentaire et facilited 'intubation. Résultats Dans les cas de voies ae´riennes normales, les temps (moyenne [e´cart interquartile]) jusqu'a`intubation trache´ale e´taient plus courts avec le Pentax-AWS (12,1 [10,1-14,4] sec) et le GlideScope (14,3 [12,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]6] sec) qu'avec le laryngoscope Macintosh (16,5 [13,,1] sec) (P \ 0,03 pour les deux). La diffe´rence de temps entre les deux vide´olaryngoscopes n'e´tait pas significative d'un point de vue statistique.…”
Section: Résuméunclassified
See 1 more Smart Citation
“…Les donne´es suivantes ont e´te´mesure´es et enregistre´es : temps jusqu'a`intubation trache´ale re´ussie (crite`re d'e´valuation principal), taux de re´ussite global, temps jusqu'a`visualisation des cordes vocales, pourcentage d'ouverture glottique, compression dentaire et facilited 'intubation. Résultats Dans les cas de voies ae´riennes normales, les temps (moyenne [e´cart interquartile]) jusqu'a`intubation trache´ale e´taient plus courts avec le Pentax-AWS (12,1 [10,1-14,4] sec) et le GlideScope (14,3 [12,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]6] sec) qu'avec le laryngoscope Macintosh (16,5 [13,,1] sec) (P \ 0,03 pour les deux). La diffe´rence de temps entre les deux vide´olaryngoscopes n'e´tait pas significative d'un point de vue statistique.…”
Section: Résuméunclassified
“…In previous studies, it has been demonstrated that the Pentax-AWS improves the glottic view and is a useful device in patients with predicted difficult tracheal intubation. [2][3][4][5][6] We have previously shown that the Pentax-AWS is an effective tool for performing tracheal intubation on a mannequin without interrupting chest compressions. 7 In other studies, it has been reported that the Pentax-AWS is a more effective device than the Macintosh laryngoscope for the performance of tracheal intubation during uninterrupted chest compressions.…”
Section: Résumémentioning
confidence: 99%
“…43,44 A defining characteristic of the videolaryngoscopic techniques is the indirect view of the glottic opening rather than the direct line-of-sight from the eye to the target using direct laryngoscopy. Some of the videolaryngoscopic techniques require an unobstructed line-ofsight from the tip of the device to the target for optimal function, whereas others can bypass obstructions in the airway lumen.…”
Section: The University Of Ottawa Airway Rotationmentioning
confidence: 99%
“…It is often used to solve the problem of the difficult airway, yielding a high rate of successful intubation and few complications (Pott and Murray, 2008). Our study showed that the Disposcope endoscope could truly achieve a comfortable and safe endotracheal intubation for patients in whom glottis viewing was difficult.…”
Section: Discussionmentioning
confidence: 74%